2007
DOI: 10.1002/ajpa.20709
|View full text |Cite
|
Sign up to set email alerts
|

Oral and physiological paleohealth in cold adapted peoples: Northeast Asia, Hokkaido

Abstract: This paper examines variables useful in reconstructing oral (caries, antemortem tooth loss, alveolar defects) and physiological (cribra orbitalia, linear enamel hypoplasia) well-being in two bioarchaeological assemblages from Hokkaido, Japan: Okhotsk (n = 37 individuals) and Jomon (n = 60). Findings are compared and contrasted with each other, with published series from Honshu Japan, and samples from climatically near-equivalent Alaska. It was found that more meaningful comparisons of Hokkaido paleohealth coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 47 publications
1
30
1
Order By: Relevance
“…The comparatively low prevalence of caries in Ngaraangbal tribes was related to a high proportion of marine foods (Elvery et al 1998). Marine diets are thought to be cariostatic due to increased fluoride levels, and due to the antibacterial effects of increased alkalinity in the oral cavity (Sealy et al 1992;Oxenham and Matsumura 2008).Contrasting with Australians, the Greenlander sample studied here is free of caries. The lack of caries in Arctic populations has been reported previously; no caries was found in Aleuts, and a prevalence of less than 1-5% in Greenlanders subsisting on a traditional diet (Pedersen 1947;Keenleyside 1998).…”
mentioning
confidence: 80%
“…The comparatively low prevalence of caries in Ngaraangbal tribes was related to a high proportion of marine foods (Elvery et al 1998). Marine diets are thought to be cariostatic due to increased fluoride levels, and due to the antibacterial effects of increased alkalinity in the oral cavity (Sealy et al 1992;Oxenham and Matsumura 2008).Contrasting with Australians, the Greenlander sample studied here is free of caries. The lack of caries in Arctic populations has been reported previously; no caries was found in Aleuts, and a prevalence of less than 1-5% in Greenlanders subsisting on a traditional diet (Pedersen 1947;Keenleyside 1998).…”
mentioning
confidence: 80%
“…Comparing with the mainland Jomon hunter-gatherers, the Okhotsk populations had better oral health (Oxenham and Matsumura, 2008), lower frequency of linear enamel hypoplasia (Oxenham and Matsumura, 2008), greater demographic proportion of elderly individuals , and larger body height (Kudaka et al, 2013). Marine mammals provided abundant fat, which is one of the most important energy sources for northern hunter-gatherer populations (Cordain et al, 2000).…”
Section: The δmentioning
confidence: 99%
“…Marine mammals provided abundant fat, which is one of the most important energy sources for northern hunter-gatherer populations (Cordain et al, 2000). Although several studies have suggested the frequent appearance of cribra orbitalia (Oxenham and Matsumura, 2008) and heavy workload in the Okhotsk culture compared with the skeletal populations of mainland Japan, the maritime dietary adaptation apparently enabled the Okhotsk people to settle in the harsh northern environment along the coast of the Sea of Okhotsk.…”
Section: The δmentioning
confidence: 99%
“…There has been little bioarcheological research on the Okhotsk people; Kodama (1948) mentioned severe dental wear and Yamaguchi (1995) identified a wound caused by a stone arrowhead in the right hip bone of a male specimen. Recently, oral health has attracted attention (Ishida et al, 1994;Hudson, 2004;Fukumoto et al, 2007;Oxenham and Matsumura, 2008;Hoover and Matsumura, 2008). However, only vertebral compression fractures were reported with regard to the skeletal system of the Okhotsk people (Ishida et al, 1994;Ishida and Matsumura, 2000).…”
Section: People From Okhotsk Culturementioning
confidence: 99%